2020
DOI: 10.1038/s41416-020-0808-8
|View full text |Cite
|
Sign up to set email alerts
|

Ferritin in glioblastoma

Abstract: Elevated levels of serum ferritin (SF) are observed in several types of cancer; however, little is known on the association between ferritin and glioma, the most frequent type of human primary brain tumour. Here we report that GBM patients show significantly increased pre-surgical SF levels (i.e. ferritinaemia) within the SF reference range and a marked ferritin immunoreactivity of resected tumour tissue. Our findings account for an indirect association between ferritin synthesis in glioma-tissue and altered S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…Ferritin, composed of ferritin heavy chain (FTH1) and ferritin light chain (FTL), is an iron storage protein in cells. Recent findings strongly support the hypothesis that glial tumors synthesize and secrete ferritin ( 26 , 27 ). Iron requirements are increased in glioblastoma stem cells, so high levels of cytoplasmic ferritin may protect cells from ferroptosis by enhancing iron chelation ( 28 ).…”
Section: Regulation Of Ferroptosis In Gliomasupporting
confidence: 66%
See 1 more Smart Citation
“…Ferritin, composed of ferritin heavy chain (FTH1) and ferritin light chain (FTL), is an iron storage protein in cells. Recent findings strongly support the hypothesis that glial tumors synthesize and secrete ferritin ( 26 , 27 ). Iron requirements are increased in glioblastoma stem cells, so high levels of cytoplasmic ferritin may protect cells from ferroptosis by enhancing iron chelation ( 28 ).…”
Section: Regulation Of Ferroptosis In Gliomasupporting
confidence: 66%
“…The higher the grade of glioma, the correspondingly stronger the treatment resistance effect it has. Purified ferritin from glioblastoma-derived cell line has marked apoptosis-stimulating activity and are inhibited by neutralizing anti-ferritin antibody Ab rH02, however, isoferrin released from cultured neonatal astrocytes did not show this activity, suggesting that the transition of astrocytes to a malignant phenotype is accompanied by alterations in iron metabolic processes ( 26 ). And research demonstrated that the extent of TfR expression in glioma is positively correlated with tumor grading ( 29 ).…”
Section: Regulation Of Ferroptosis In Gliomamentioning
confidence: 99%
“…The association between high-grade glioma and iron metabolism has been reported previously. Jaksch-Bogensperger et al showed that patients with high-grade glioma have higher serum ferritin levels (12). Glioblastoma cancer stem-like cells can absorb iron from the microenvironment more effectively, by upregulating their expression levels of ferritin and transferrin receptor 1 (8).…”
Section: Introductionmentioning
confidence: 99%
“…Ferritin is an iron storage protein whose level reflects the iron reserve and iron load in the body (Golan et al, 2021). It is elevated during infectious diseases, tumors and inflammation (Jaksch-Bogensperger et al, 2020;Kim et al, 2013). Studies have shown that iron at high concentration could accelerate the formation of free radicals and oxidation of atherogenic lipoproteins such as cholesterol (Cozzi et al, 1990;Ikeda et al, 2006;Tuomainen et al, 2003).…”
Section: Introductionmentioning
confidence: 99%